Catalan Legal Mind and the Legal Catalan Mind. A brief overview on Legal and Political Principles - Casanovas, Pompeu (Journal of Catalan Intellectual History, 2011)
This paper constitutes a short introduction to Catalan political and legal thought. I have tried to summarize the essentials of a particular way to understand institutions, legal systems and political behavior which are historical in nature. Several researchers, historians, jurists, and political scientists are addressing the traditional subject of Catalan pactism with a renewed interest. This paper is conceived as a reflection on this trend. I distinguish between ‘Catalan legal mind’ and ‘the Legal Catalan Mind’ which started up at the beginning of the 16th c., was consolidated during the 17th, and eventually produced what is known as “political pactism” in the 19th c. and 20th c. key words legal pactism, late legal pactism, Catalan legal mind, legal Catalan mind, political pactism, Catalan legal tradition, imperialism, modern state, Spanish political thought, Krausism, modernism.